1990
DOI: 10.1210/jcem-70-5-1431
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biochemical Markers of Osteoblastic Activity during the Menstrual Cycle*

Abstract: Serum levels of osteocalcin [OC; bone Gla protein (BGP)] and bone alkaline phosphatase (B-AP) are both correlated to osteoblastic activity, which may be regulated by several hormones, including estrogen, 1,25-dihydroxyvitamin D3 [1,25-(OH)2D3], and PTH. Estrogen shows reproducible variations during the menstrual cycle, while available data on variations in serum 1,25-(OH)2D3 and serum immunoreactive PTH show midcyclic increases or no changes. In the present study we evaluated osteoblastic activity by measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
5
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 20 publications
5
59
5
2
Order By: Relevance
“…This is in agreement with the findings of Schlemmer et al (6) and Tjellesen et al (5) but different from those of Nielsen et al (4) who reported an increase in serum OC and BAP during the LP in eight premenopausal women. Gorai et al (8) found differences in serum BAP between subphases of the menstrual cycle, but these did not show an overall FP-LP difference and did not seem to form a consistent pattern because values were generally higher nearer to day 0 but low at day 0 itself.…”
Section: Figsupporting
confidence: 89%
See 4 more Smart Citations
“…This is in agreement with the findings of Schlemmer et al (6) and Tjellesen et al (5) but different from those of Nielsen et al (4) who reported an increase in serum OC and BAP during the LP in eight premenopausal women. Gorai et al (8) found differences in serum BAP between subphases of the menstrual cycle, but these did not show an overall FP-LP difference and did not seem to form a consistent pattern because values were generally higher nearer to day 0 but low at day 0 itself.…”
Section: Figsupporting
confidence: 89%
“…Our results are in agreement with two published studies (33,34) but do not agree with four others. (35)(36)(37)(38) The reasons our correlations of bone markers with E 2 and P differ from those reported in other studies (4,8) are not entirely clear. Those studies did not report whether calculated correlations were from multiple data points per woman or whether they were within woman or between women.…”
Section: Figmentioning
confidence: 81%
See 3 more Smart Citations